THE STANDARDISATION OF ANATOMICAL, HISTOLOGICAL AND EMBRYOLOGICAL TERMINOLOGY IN TRANSLATING ENGLISH-BASED ANATOMY TEXTBOOK INTO INDONESIAN: STANDARDISASI TERMINOLOGI ANATOMI, HISTOLOGI DAN EMBRIOLOGI DALAM MENERJEMAHKAN BUKU TEKS ANATOMI BERBASIS BAHASA INGGRIS KE BAHASA INDONESIA - Anggraini, Wita (TALENTA, 2017)
Anatomical terminology is derived from classical languages, primarily Latin. Latin was used as the language of science until the early 18th century, so all medical textbooks were previously written in Latin. The existence of Latin in the textbooks of anatomy-histology-embryology in Indonesia becomes a challenge for students, lecturers, and researchers because they often have no background knowledge of Latin. The gap in Latin makes English textbooks preferable. English-based anatomy textbooks have been widely translated into Indonesian, but the translation of anatomical terminology in English has no standardization yet. The translations of anatomical terms can be based on several sources, namely: (1) Nomina Anatomica, Nomina Histologica, and Nomina Embryologica; (2) Terminologia Anatomica (TA), Terminologia Histologica (TH), and Terminologia Embryologica (TE); (3) Absorption language by adopting Latin and writing the anatomical terms in accordance with Indonesian spelling; and (4) Translation from English to Indonesian. The aim of this paper was to initiate the selection and determination of the anatomical terms which should be used in Indonesian in order to translate the English-based anatomy textbooks.